Climate-Smart Agriculture (CSA) within the Feed the Future Project Portfolio of USAID-Bangladesh: A CCAFS Deep-Dive Review - White, Douglas; Quinney, Marie; Jarvis, Andy (2016)
As part of a global effort that will inform how Feed the Future tracks CSA across the 19 focus countries (plus aligned) the CCAFS and USAID/BFS team selected 5 to carry out a deeper analysis of their portfolio. A visit in August 2015 by personnel from CCAFS and USAID-BFS Washington to the Bangladesh Mission provided an opportunity to identify and discuss CSA-related activities within the country and the USAID zone of influence (ZOI). The five-day visit included a series of meetings with Mission staff, project implementing partners and the Bangladesh Department of Agricultural Extension. While the discussion scope emphasized the second of the above CSA objectives, adaptation, within Feed the Future (FTF) projects, the meetings included discussion of the other CSA objectives and USAID projects associated with Food for Peace and Global Climate Change. The visits were preceded by a document review of the Bangladesh Mission projects and relevant agriculture and climate change information available on the web. This report outlines key findings of the visit and suggests ways in which CSA can be further integrated into upcoming Feed the Future programming in Bangladesh.